Organization of First Aid in the Arkhangelsk Region - A. V. Baranov (Неотложная медицинская помощь)
Background The development and implementation of widespread training for rules, techniques and methods of providing first aid to the widest possible range of people will significantly reduce the level of disability and mortality among victims of road traffic accidents (RTAs).Aim of study To study the organization of first aid for the victims in the Arkhangelsk region.Material and methods Part 1. The journals of registration of attendance at classes with a trained contingent in the educational-methodical department of the School of Disaster Medicine of the Territorial Center for Disaster Medicine of the Arkhangelsk Region for the period from 01.01.2012 to 12.31.2018 are analyzed. Part 2. We selected 906 medical records of patients (003/u) affected by an accident on the federal highway M-8 “Kholmogory” and treated in hospitals of Arkhangelsk region, admitted acutely in period from 01.01.2012 till 31.12.2018. The study was conducted according to the criteria of retrospective continuous documentary observation. As a criterion of statistical significance, the probability of a random error of less than 5% (p<0.05) was applied using the correction for multiple comparisons (Bonferroni correction).Conclusion 1. The educational activities of the TCDH of the Arkhangelsk Region over a seven-year period are characterized by a significant increase in the total number of trained cadets (p<0.001); 2-fold increase in the number of trained motor vehicle drivers (p<0.001) and employees of Ministry of Emergency Situations and Russian Interior Ministry (p<0.001). 2. The first aid to injured in an accident on the federal highway M-8 Kholmogory in the Arkhangelsk Region was provided in 65 cases (7.2%); in almost 90% of cases, first aid was recorded in the Arkhangelsk and Severodvinsk medical districts of the Arkhangelsk region (p<0.001).